Procedimento de desenvolvimento de novos produtos no setor agrícola - Santos, Renan dos (2023)
The products developed are the main means for a company to convey its values to customers and thus achieve the organization's objectives. However, product strategies contain complex decisions that interfere and condition the organization, both internally and externally. The development of new products, or any change in the product portfolio, requires the commitment of the functional areas to reflect, in an integrated and cohesive manner, the offer provided to the market. Currently companies seek to develop and expose new products in a short period of time, taking this into account, the project management model must be well established, based on an entry strategy and be consolidated by the validation stages. Through a bibliographic review in the areas of management and validation of the functional part of the project, a concept model for managing new opportunities in this sector is presented; which proved, through theoretical comparisons and practical experimentation, that the established strategic mapping, not only standardized the entry, but also streamlined the internal process in conducting new demands, in a continuous and parallel flow of steps, also guaranteed a better functionality of the equipment analyzed and adjusted. In this way, it expanded experimentation to other important stages in the elaboration of a product in the agricultural sector in Brazil.